Growth and mortality of Osteogeneiosus militaris (Linnaeus 1758) from Mumbai waters - Parida, Pranaya Kumar; Jaiswar, A. K.; Palaniswamy, R.; Kumar, Pawan; Chakraborty, S. K. (Indian Journal of Fisheries, 2014)
Based on the length frequency data collected during the period January 2002 to August 2004, the growth and mortality parameters of Osteogeneiosus militaris was estimated. The asymptotic length (L âˆž ), growth coefficient (K) and t o were estimated as 583 mm, 0.67 yr -1 , and -0.0396 years respectively. Based on the von Berttalanffy growth (VBG) parameters, the growth of the fish during 1 to 5 years of its age works out to be 292, 426, 487, 516, and 529 mm respectively. The growth performance index was estimated as 3.55. The instantaneous rate of total mortality was estimated as 3.55, natural mortality as 1.04 and fishing mortality as 2.51. The phi prime was estimated as 3.35. The exploitation ratio (U) and exploitation rate (E) were worked out as 0.67 and 0.70 respectively. The vulnerability of catfish in general and O. militaris in particular with respect to over-exploitation, destruction of eggs, incubating males and the inherent low fecundity of the family are discussed in the present communication.